Nitrogen Rationing and Scheduling to Improve Yield of Wheat in Nitrogen Deficit Soil of Southwest Bangladesh: Nitrogen Rationing in Nitrogen Deficit Soil - Chaity, Mahbuba Yesmeen; Ali, Md Yasin; Jahan , Md Sarwar (South Asian Journal of Agriculture, 2025)
Nitrogen (N) is an important macro nutrient element for crops and its availability to plants largely vary on soil properties and overall soil environment such as soil temperature, soil moisture, microbial population etc. Its available forms NO3- and NH4+ both are very much mobile in plants and NO3- is mobile in soils but ammonium (NH4+) has a low mobility in soil due to its positive charge, which attracts it to negatively charged soil particles and organic matter. So, N recommendation should be not only crop spacific but also soil spacific and season spacific. Keeping this fact in mind, an experiment was conducted at the Dr. Purnendu Gain Field Laboratory of Agrotechnology Discipline, Khulna University, Khulna during November 2016 to March 2017 to optimize rationing and scheduling of nitrogen for wheat in a N deficit coastal soil. Growth and yield parameters of BARI Gom-25, a salt tolerent variety, was assessed. The experiment was laid out in randomized complete block design (RCBD) with four N levels i.e. D0 = 0 kg ha-1, D1 =50 kg ha-1(50% less), D2 =100 kg ha-1(recommenrded), and D3 = 150 kg ha-1(50% more) in factorial combination with three N application time ( T1= 66:34:0, T2= 34:33:33, T3= 0:50:50 applied at basal, crown root initiation (CRI) stage (25DAS) and jointing stage(45DAS), respectively) as treatments with three replications. Experimental data on dry matter partitioning (leaves, stem, flag leaf and spike dry weight plant-1 at different days after sowing), crop phenology, yield and yield attribute were collected and analyzed statistically. The results revealed that the different rate and time of N application had significant effect on all the parameters of the experiment. Nitrogen at 150 kg ha-1 (D3) with 2 splits application (T1) contributed to highest dry matter accumulation in leaves at 60 DAS (5.19 g), in stem at 70 DAS (11.47 g) and in flag leaf at 80 DAS (2.30 g) then these were decreased up to harvest. Spike dry weight was increased gradually and reached the peak at the time of harvest (3.86 g) at 100 kg N ha-1 with 2 splits (T1). Days to flowering and days to maturity were delayed due to application of extra N (D3). Growth parameters were found to be higher at 150 kg N ha-1 with 2 splits application (D3T1). Yield and yield contributing characters except unfilled grain spike-1 and straw yield were found higher at 100 kg N ha-1 with 2 splits application (D2T1) and the highest grain yield (4.27 t ha-1) was obtained from this treatment combination. The highest straw yield (5.67 t ha-1) was obtained from D3T1 treatment combination. Higher agronomic N use efficiency (35 kgkg-1) was observed in D1T1followed by D2T1(32.7 kgkg-1) and the highest relative economic return (102659 Tk) was in D2T1 followed by D2T2 (94926 Tk) treatment combinations. Thus, 100 kg N with 2 splits (T1 = 66:34:0) application at basal and CRI stage(25DAS) could be the optimum N application schedule for wheat in N deficit soil of southwest Bangladesh. South Asian J. Agric., Vol. 11, No.1, 2025: 24-37